Genetic Divergence of Lineage-Specific Tandemly Duplicated Gene Clusters in Four Diploid Potato Genotypes - Bonthala, Venkata Suresh; Stich, Benjamin (Frontiers in Plant Science, 2022)
Potato (Solanum tuberosum L.) is the most important non-grain food crop. Tandem duplication significantly contributes to genome evolution. The objectives of this study were to (i) identify tandemly duplicated genes and compare their genomic distributions across potato genotypes, (ii) investigate the bias in functional specificities, (iii) explore the relationships among coding sequence, promoter and expression divergences associated with tandemly duplicated genes, (iv) examine the role of tandem duplication in generating and expanding lineage-specific gene families, (v) investigate the evolutionary forces affecting the tandemly duplicated genes and the evolutionary fates of tandemly duplicated genes during subsequent evolution, and (vi) investigate the similarities and differences in above mentioned aspects between cultivated genotypes and their wild-relative. In this study, we used well annotated and chromosome-scale de novo genome assemblies of multiple potato genotypes. Our results showed that the tandemly duplicated genes are abundant and dispersed through the genome. We found that several functional specificities such as disease resistance, stress-tolerance and biosynthetic pathways of tandemly duplicated genes were differentially enriched across multiple potato genomes. Our results indicated the existence of a significant correlation among expression, promoter and protein divergences in tandemly duplicated genes. We found about one fourth of tandemly duplicated gene clusters as lineage-specific among multiple potato genomes, and tend to localize towards centromeres and had distinct evolutionary and expression patterns. The lineage-specific expansion of gene families by tandem duplication coupled with functional bias might have significantly contributed to evolution of the genome for adaptive evolution against environmental stimuli in potatoes.